if p q r are in ap and x y z are in gp then x^q-r.y^r-p.z^p-q is equal to ?
Answers
Answered by
128
answer is one . as x y z are in gp so
![y = \sqrt{xz } = > y^{2} = xz y = \sqrt{xz } = > y^{2} = xz](https://tex.z-dn.net/?f=y+%3D++%5Csqrt%7Bxz+%7D++%3D++%26gt%3B+y%5E%7B2%7D++%3D+xz)
............ (1)
now p q r are in ap so
q-r = -d. r-p = 2d and p-q = -d
so.
![x ^{ - d} .y^{2d} . {z}^{ - d} = {x}^{ - d} {z}^{ - d} . {y}^{2d} x ^{ - d} .y^{2d} . {z}^{ - d} = {x}^{ - d} {z}^{ - d} . {y}^{2d}](https://tex.z-dn.net/?f=x+%5E%7B+-+d%7D+.y%5E%7B2d%7D+.+%7Bz%7D%5E%7B+-+d%7D++%3D+++%7Bx%7D%5E%7B+-+d%7D+%7Bz%7D%5E%7B+-+d%7D+.+%7By%7D%5E%7B2d%7D++)
so it becomes
= {y^2 / xz}^d = 1^d = 1 ...... from eqn (1)
............ (1)
now p q r are in ap so
q-r = -d. r-p = 2d and p-q = -d
so.
so it becomes
= {y^2 / xz}^d = 1^d = 1 ...... from eqn (1)
Answered by
120
Thank you for asking this question. Here is your answer:
p,q,r are in AP so 2q = p+r
and x,y,z are in gp so y² = xz
Now x^q-r y^r-p z^p-q = x^(p+r/2-r) y^r-p z^(p-(p-r)/2)
= x^(p-r/2) . y^r-p z^(p-r/2)
= x^(p-r/2) . (xz)^(r-p)/2 z^(p-r/2)
= x^(p-r/2) . x^(r-p/2) z^(r-p/2) z^(p-r/2)
= x^0 z^0
= 1
If there is any confusion please leave a comment below.
Similar questions